Parental support as a moderating variable in the relationship of academic resilience and academic stress to academic burnout in medical clerkship students - Endang Suci Lestari; Nur Ainy Fardana Nawangsari; Suryanto Suryanto (Faculty of Psychology Universitas Islam Sultan Agung Semarang, 2026)
Academic burnout, manifested through psychological exhaustion, cynical attitudes, and perceptions of helplessness, is a common phenomenon among medical education students. This quantitative study aims to examine the relationship between academic resilience and academic stress with academic burnout, as well as to investigate the moderating role of parental support. Data were collected using the Maslach Burnout Inventory-Student Survey, the Academic Resilience Scale (ARS-30), the Student Life Stress Inventory, and The Social Provisions Scale. Data analysis techniques employed moderated regression analysis and interaction effects, utilizing data transformation (centering) and the PROCESS macro-Hayes Model (Model 1). Based on findings from 112 participants selected through purposive sampling, moderation regression analysis (PROCESS Model 1 Hayes) revealed that academic resilience had a significant negative effect (β = -0.245; p < 0.001), while academic stress had a significant positive effect (β = 0.346; p < 0.001) on academic burnout. Parental support was found to significantly moderate both relationships. Parental support acted as an effective buffer by weakening the positive relationship between academic stress and academic burnout (interaction β = -0.0111; p < 0.001; ΔR² = 6.70%). However, parental support weakened the negative relationship between academic resilience and academic burnout (interaction β = 0.0354; p < 0.001; ΔR² = 9.65%), and at high levels of support, academic resilience was no longer a significant predictor. This indicates that excessive support has the potential to hinder the development of students' internal capacities. The research model explained 68.8% of the variance in academic burnout, implying the need for a balanced approach that simultaneously strengthens external support and develops internal resilience.